The means and aesthetics of image formation in Arif Al-Saadi's poetry - AlBadri, Shazi; Siddiqi, Bahar; AlKhazraji, Abdul Baqi (Al-Adab Journal, 2023)
Poetry is a single structure that is coherent with each other and is coherent in terms, we cannot think about details or separate elements. The poetic image in the mind of the producer and the recipient alike is of the highest degree of importance in terms of the exchange of roles in my productions, before the creator, after moments of reflection and creativity, during certain reactions in life, nature, and the environment of the creator of the text, through the transmission through the channels of the poetic language that transcends logic and violates the laws of language. Naturalism is a defect in the mentality of the receiver, who in turn works on the process of separation based on this image in a completely opposite process to the formations before the product. In this study, we have focused on the poet Arif al-Saadi as one of the most important poets of the 19th generation movement, and he is a leading poet in the field, who gained wide and important fame during his poetic works and over a period of more than two decades, and is still a fertile ground for extremely important cognitive and cultural levels, and for the study of experience. Ikhtarna's poetry expresses the aesthetic means of the image in my poem, sending feelings and recognition. That means the transmission of senses (an expression that indicates the sensory perception or describes the sensory perception of a particular sense in the language of another sense) or borrowing a sense to function as a description of another sense. It becomes fragrant visuals, and in that the expression of feelings (so that all human senses interact in the crucible of feelings, which takes the emotional state and illuminates the pictorial burst, and the various cards add beauty and clarity to the picture through the interaction between the different senses that make up consciousness and feeling. Sending emotions gives the poet the opportunity to exploit inspiration in one or more senses, thereby intensifying the poem and focusing in the desired direction, in addition to this, sending emotions enriches the language. It also means that the poet moves away from the usual context of the word that expresses our feeling, and transfers it to other words of feeling, thereby diversifying the ways of expressing the same feeling Poetry text. But the identification: it is the color of the colors of the metaphorical image, and it is a stylistic feature of the transference of all the things from the worlds to the last world, pulsing with life, and the poetic text acquires a special poetic quality, because it has a spiritual power, in addition to the power, to influence the mind of the recipient.